THE DEVELOMENT OF MARKETING STRATEGY MODEL FOR ENTREPRENEURS OF GOYOR WOVEN FABRIC INDUSTRY - Suranto Suranto; Adcharina Pratiwi; Agus Marimin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to: (a) formulate a sales media-based marketing strategy to increase sales of Goyor fabric at Sragen Goyor Industry Center, (b) analyze the increase in the sales volume of Goyor fabric based on sales media at Sragen Goyor Industry Center. The advantages of this research are: (a) the formulation of a marketing strategy model based on sales media with goodness of fit model is produced, (b) the trend of Goyor sales during model development is known. This research method uses a mix method, namely qualitative to collect a number of information in solving the problems encountered by Goyor entrepreneurs in Sragen and a quantitative approach to analyze the sales media-based marketing model. The media-based marketing model includes: (1) web creation, (b) tik tok, (3) instagram, (4) financial system, (5) billboard, (6) facebook, (7) prduct catalog, (8) marketing digitization. Sales media is uded to determine the importance of marketing indicators and marketing volume including indicators . The results of the marketing strategy model assistance through the media, produced: (1) the formulation of a sales media-based marketing strategy model that is goodness of fit model, and deserves to be a good marketing model, (2) the sales trend through the developed media has increased. The marketing strategy formulation model developed can be implemented in Sragen goyor fabric. industry center.